Earnings Quality and Investment Efficiency: Evidence from Eastern Europe - Victoria Cherkasova; Daryush Rasadi (Review of Economic Perspectives, 2017)
This study explores the firm-level relationship between earnings quality and investment efficiency. Higher quality of reported results has the capacity to positively impact the efficiency of company's investment levels by over- and underinvestment reduction. The research is carried out on the sample of 7546 companies from Eastern Europe for the period 2010-2015. Eastern European countries have a unique institutional and business environment that is relevant to the purpose of this paper. We divide the sample into 2 fundamentally different economic sectors - industrial and retail - and test the significance of each factor in the main relationship. We also examine the factor of the firm's ownership form by comparing earnings quality with investment efficiency values between public and private companies. Our main results show that a higher earnings quality mitigates both overinvestment and underinvestment issues. The relationship between earnings quality and underinvestment turns out to be stronger in the industrial sector. As for the comparison of public and private firms, public companies on average demonstrate a higher earnings quality and lower overinvestment issues.
Keywords: 330; Earnings quality; financial reporting quality; investment efficiency; overinvestment; underinvestment